2017
DOI: 10.1590/0100-3984.2015.0194
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls and artifacts in the interpretation of oncologic PET/CT of the chest

Abstract: PET/CT is widely used for the evaluation of patients with thoracic malignancies. Although the levels of 18F-fluorodeoxyglucose (FDG) uptake are usually high in neoplastic diseases, they can also be physiological, due to artifacts. In addition, FDG uptake can occur in benign conditions such as infectious, inflammatory, and iatrogenic lesions. Furthermore, some malignant tumors, such as adenocarcinoma in situ (formerly known as bronchoalveolar carcinoma) and carcinoid tumors, may not show FDG uptake. Here, we il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some reports also indicate that PET with 18 F-FDG has potential as a screening method for cancer and can detect new malignant tumors that other imaging methods fail to detect in asymptomatic individuals ( 24 , 25 ) . The PET/CT combination is a promising hybrid imaging modality that is being used routinely in different clinical situations ( 26 - 29 ) , because it allows precise integration of metabolic PET images with high-quality CT images in an acquisition that goes from the top of the head to the upper thigh ( 19 ) . FDG is a glucose analog used as a marker with fluorine-18, a positron-emitting radioisotope, which allows the study of the glucose metabolism because of its higher uptake by tissues with increased glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports also indicate that PET with 18 F-FDG has potential as a screening method for cancer and can detect new malignant tumors that other imaging methods fail to detect in asymptomatic individuals ( 24 , 25 ) . The PET/CT combination is a promising hybrid imaging modality that is being used routinely in different clinical situations ( 26 - 29 ) , because it allows precise integration of metabolic PET images with high-quality CT images in an acquisition that goes from the top of the head to the upper thigh ( 19 ) . FDG is a glucose analog used as a marker with fluorine-18, a positron-emitting radioisotope, which allows the study of the glucose metabolism because of its higher uptake by tissues with increased glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the mean SUV and SUV max differ according to histologic subtypes of lung cancer. In particular, it has been reported that the SUV max of carcinoid tumors and BAC are low ( 10 , 11 ). Vesselle et al ( 12 ) found that the SUV max of BAC was lower than all other subtypes, and that non-BAC adenocarcinomas had lower SUV max values than SCC.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to radiomics, feature reproducibility is of utmost importance, considering the varying image acquisition (including the highly variable CT protocols and slice thickness), preprocessing, and segmentation [86,87]. PET/CT scan undeniably provides a vast amount of imaging data and parametric information, yet it can be correlated with pitfalls and/or artifacts, while it remains more expensive and difficult from a technical requirement perspective [88]. The absence of universal consensus on the optimal threshold for LC radiomics should also be considered [89].…”
Section: Discussionmentioning
confidence: 99%